2013
DOI: 10.7883/yoken.66.497
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vaccination Dose and Clinico-Demographical Factors on Antibody Titers against Measles, Rubella, Mumps, and Varicella-Zoster Viruses among University Students in Japan

Abstract: SUMMARY:To evaluate the influence of vaccination dose and clinico-demographical factors on immune status against measles, rubella, mumps, and varicella viruses among university students, we conducted a case-control study by analyzing serum antibody titers according to past immunization and infection, and perinatal histories, using a multivariate regression model. A total of 1370 medical, paramedical, and pharmaceutical students were included in the analysis. Two or more doses of measles and rubella vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Comparing our data with those of the CDC report, the immunity level for measles is nearly the same and the immunity level for rubella is slightly lower. A Japanese study of the immunity level for rubella was also reported to be the same as those of the CDC report [14]; thus, the reason the immunity level for only rubella is lower in the present study is unclear.…”
Section: Discussionsupporting
confidence: 59%
“…Comparing our data with those of the CDC report, the immunity level for measles is nearly the same and the immunity level for rubella is slightly lower. A Japanese study of the immunity level for rubella was also reported to be the same as those of the CDC report [14]; thus, the reason the immunity level for only rubella is lower in the present study is unclear.…”
Section: Discussionsupporting
confidence: 59%
“…Twenty-eight papers were obtained: 3 review articles, 4 - 6 17 original articles, 7 - 23 2 brief reports, 24 , 25 2 letters, 26 , 27 1 research note, 28 and 3 proceedings 29 - 31 (see Table 1 ). Additionally, all the articles were in English, and all the proceedings were from an international conference.…”
Section: Resultsmentioning
confidence: 99%
“…These factors are used as adjusting confounding factors (eg, birthplace, gestational week, and neonatal asphyxia) in research about preventing infectious disease. 15 Moreover, vaccination coverage can be the main outcome in research studies by using the vaccination history from the MCHH. 16 - 18 Vaccination history is important, as it can record the immunity status for preventing infectious disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, subjects with a history of measles and mumps tended not to be immunized. Although some people had measles or mumps history, their immune status was not confirmed by serological test [ 19 , 20 ]. In practice, measles’s clinical diagnosis is often challenging, especially in secondary measles vaccine failure [ 21 ].…”
Section: Discussionmentioning
confidence: 99%